Social Media Applications For Independence Economy - Ellina Rienovita; Dian Ariani; Josua Sahala; Jacomina Vonny Litamahuputty; Junus Paulus Patty (Pusat Riset dan Inovasi Nasional, 2023)
A considerable advancement has been achieved in Indonesia's digitalization process. The increase in internet users after the epidemic has facilitated the world's transition to a digital society. The real-time transfer of information from remote regions of Garut Regency to England is made possible by technological advancements. If this material is shared via social media, it can be promptly accessed by a larger audience. This has led to the creation of new jobs, such as those for content creators who use social media to assist media networks, particularly young people, in becoming financially independent. Since 2022, there has been an increase in internet users in locations like Garut, West Java. Still, the primary industries providing Garut Regency's citizens with money are agriculture, livestock, textiles, and fishing. This project aims to give the younger generation in Garut Regency a new social media paradigm that includes new revenue streams. The first awareness-raising campaigns made the younger generation in Garut Regency aware of the use of social media as a means of encouraging economic independence. Second, the content development sector is expanding in the Garut Regency.